Developing smart ICT in rural communities in Malaysia through the establishment of telecenters - Zurinah Tahir,; Jalaluddin Abdul Malek,; Mohd Asruladlyi Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The adoption of information and communication technology (ICT) is among the primary agendas of the Malaysian government to raise the national economy and to transform its populace to be more technologically oriented. The rapid expansion of ICT in the process of rural development is evident both locally and globally. In line with national aspirations, the government addressed the challenge of ICT through a programme in which telecentres were set up in rural communities. The cyberworld was introduced to the countryside through telecentres which offered online facilities, world exposure and learning to the rural population with the aim of narrowing the digital gap between the rural and the urban folk. Studies have shown that urbanisation of rural areas through the setting up of telecentres produces a positive impact; there is holistic development that nurtures a technology-savvy generation. Hence, this study examines the impact of the telecentre programme on the development of rural areas through the implementation of Smart ICT.